Morphology of powder particles produced by spray atomization and other processes - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The physical and mechanical properties of coatings are heavily influenced by the technologies of powder production and by the parameters of the plasma spray process. One of the most important parameters that affects the physical and mechanical properties of coatings is the morphology of powder particles - homogeneity, granulation and granulation range, directly related to the technologies of powder production. This paper describes the technological processses of powder production most commonly used and shows the SEM micrographs of powder morphologies. Depending on the manufacturing process, powder particles have different characteristics regarding their shape, size, specific gravity, purity, etc. Since these characteristics have a significant impact on the quality and properties of deposited coatings, it is necessary to possess knowledge about the characteristics of powders in order to better control the behavior of particles in the plasma jet, in order to produce the expected characteristics of the coating.Powders have a variety of characteristics to be set for the operating parameters of the deposition in order to obtain the desired coating characteristics.
Keywords: property; powders; particles; Mechanical Properties; Coatings; characteristics